2020
DOI: 10.3390/ani10122374
|View full text |Cite
|
Sign up to set email alerts
|

Genera and Species of the Anisakidae Family and Their Geographical Distribution

Abstract: Nematodes of the Anisakidae family have the ability to infest a wide variety of aquatic hosts during the development of their larval stages, mainly marine mammals, aquatic birds, such as pelicans, and freshwater fish, such crucian carp, these being the hosts where the life cycle is completed. The participation of intermediate hosts such as cephalopods, shrimp, crustaceans and marine fish, is an important part of this cycle. Due to morphological changes and updates to the genetic information of the different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 148 publications
0
25
0
3
Order By: Relevance
“…Anisakidae, the largest family of nematodes, displaying zoonotic importance, currently represented by 46 species worldwide (Ángeles-Hernández et al, 2020), presents 23 fish parasitic species reported in Brazil, five of them in the Amazon region (Luque et al, 2011). A record of Anisakis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Anisakidae, the largest family of nematodes, displaying zoonotic importance, currently represented by 46 species worldwide (Ángeles-Hernández et al, 2020), presents 23 fish parasitic species reported in Brazil, five of them in the Amazon region (Luque et al, 2011). A record of Anisakis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Anisakidae is a family of nematode worms that are zoonotic and can infest a variety of aquatic biota during the development of their larvae, including marine mammals, pelicans, cephalopods, renic shrimp and sea fish. (Ángeles-Hernández et al, 2020;Guan et al, 2021). The dominant predilection of Anisakidae is in the viscera body cavity of the host and is minorly in the muscles of fish (Piras et al, 2014).…”
Section: Anisakidae Distribution In Indonesiamentioning
confidence: 99%
“…The existence of differences in the character of these waters cannot be used as a specific determining factor in the distribution of Anisakidae. They were considering that species of marine fish infected with Anisakidae are very diverse and come from various habitats, and the discovery of various aquatic biota infected with adult and larval Anisakidae (Bilska et al, 2015;Kuhn et al, 2016;Ángeles-Hernández et al, 2020;Siagian and Maryanti, 2020). However, through research conducted by Guan et al (2021), the temperature has a significant role in influencing the movement of larvae of Anisakis and Pseudoterranova.…”
Section: Distribution Factors "Parasite Family Anisakidae"mentioning
confidence: 99%
“…The distribution of Anisakis spp. is related to several factors, such as global warming, oceanographic conditions, water circulation, salinity percentages, and host density and migration [ 7 ]. Additionally, several species of marine fish can serve as intermediate or paratenic hosts for Anisakis spp., with the L3 encyst residing in internal tissues awaiting ingestion by marine mammals (definitive host) or humans (accidental host) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The parasitic nematodes in the Anisakidae family are very similar and are known as the complex parasitic group that is difficult to distinguish by morphological techniques. Consequently, the most accurate methods of identifying Anisakis parasites are the molecular biological methods, including polymerase chain reaction (PCR), polymerase chain reaction–restriction fragment length polymorphism, and next-generation sequencing [ 7 ]. Presently, the internal transcribed spacer (ITS) region of ribosomal DNA (ITS-1, 5.8S rRNA gene, and ITS-2) and the mitochondrial cytochrome oxidase subunit II (COII) gene are considered and recognized as molecular markers for species identification and genetic variation of anisakid nematodes [ 2 , 7 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%